Possible Tacrolimus-Related Neuropsychiatric Symptoms: One Year After Allogeneic Hematopoietic Cell Transplantation: A Case Report. Issue 15 (March 2022) - Løhde, Linda W; Bentzon, Adrian; Kornblit, Brian T; Roos, Peter; Fink-Jensen, Anders
Tacrolimus is a calcineurin inhibitor (CNI), an immunosuppressive agent used to prevent graft versus host disease following allogeneic hematopoietic cell transplantation (HCT). Side-effects of tacrolimus treatment include neuropsychiatric symptoms, for example, affective disturbances, psychosis, and akinetic mutism. The onset of side-effects is independent of tacrolimus blood concentration and can occur years after treatment initiation. To our knowledge, case-reports describing tacrolimus-induced neuropsychiatric symptoms following HCT are sparse. This article reports the case of a 60-year-old woman with T-cell prolymphocytic leukemia, who developed memory loss, affective disturbances, and delusions, 1-year after HCT, and tacrolimus treatmentinitiation. Upon hospital admission, she was motionless and mute, albeit easily roused. The routine physical examination was without pathological findings. Blood work and microbiological analyses of blood and cerebrospinal fluid were normal. The neuroimaging showed chronic structural changes without relation to the debut of neuropsychiatric symptoms. Tacrolimus was discontinued on suspicion of tacrolimus-induced neuropsychiatric symptoms. The patient recovered within 48 hours of discontinuation. She was switch to prednisone treatment, and there has been no reemergence of neuropsychiatric symptoms since.